2016
DOI: 10.1177/2211068215602191
|View full text |Cite
|
Sign up to set email alerts
|

Technologies That Enable Accurate and Precise Nano- to Milliliter-Scale Liquid Dispensing of Aqueous Reagents Using Acoustic Droplet Ejection

Abstract: Acoustic liquid handling uses high-frequency acoustic signals that are focused on the surface of a fluid to eject droplets with high accuracy and precision for various life science applications. Here we present a multiwell source plate, the Echo Qualified Reservoir (ER), which can acoustically transfer over 2.5 mL of fluid per well in 25-nL increments using an Echo 525 liquid handler. We demonstrate two Labcyte technologies-Dynamic Fluid Analysis (DFA) methods and a high-voltage (HV) grid-that are required to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 26 publications
(31 reference statements)
0
27
0
Order By: Relevance
“…A recent study has shown that41 stochastic instabilities in the droplet trajectory can occur, possibly due to variable ADE energy requirements at the surface of the source liquid surface. And minimizing the distance between the source and destination reduces the CV in droplet placement due to the reduced time during which the error in trajectory can propagate, thus improving the precision of the droplet placement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that41 stochastic instabilities in the droplet trajectory can occur, possibly due to variable ADE energy requirements at the surface of the source liquid surface. And minimizing the distance between the source and destination reduces the CV in droplet placement due to the reduced time during which the error in trajectory can propagate, thus improving the precision of the droplet placement.…”
Section: Resultsmentioning
confidence: 99%
“…Focused high-frequency sound waves create a controlled pressure wave front that can be further excited near the fluid surface to generate and eject small droplets. Due to advances in computational speed and signal processing algorithms, ADE precisely controls droplet generation to yield predefined volumes and ejection speeds4041. We then characterized and applied the automated system to report K D for a six-member library of recombinant antibodies against eGFP.…”
mentioning
confidence: 99%
“…The source plates used to transfer from were 384-well polypropylene microtiter plates. A variety of different well fluid volumes were used in the source plates (20,30,40, and 50 µL). For each source well volume studied, 20-drop transfers from 384 separate wells filled to that volume were measured, in order to obtain meaningful statistics.…”
Section: Dynamic Fluid Analysismentioning
confidence: 99%
“…27,28 The extension of the DFA methods to larger droplet size (25 nL) is described in another article in this journal, further confirming the value of DFA to bring robust liquid-transfer performance to ADE applications. 20 …”
Section: Dynamic Fluid Analysismentioning
confidence: 99%
“…20 No longer is ADE restricted to a limited range of fluids (nor does it require liquid-by-liquid individual calibrations). The development of dynamic fluid analysis, as outlined by Sackmann et al, 21 generates automatic monitoring and calibrations of the system on a well-by-well basis in milliseconds. Buffers, solvents, 50% glycerol, or detergent-based solutions are automatically transferred with the same high precision as was developed for DMSO.…”
Section: Research-article2015mentioning
confidence: 99%